2016
DOI: 10.1038/srep24021
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of emigration and their impact on survival during dispersal in fox and jackal populations

Abstract: Animals disperse in response to poor resource conditions as a strategy of escaping harsh competition and stress, but may also disperse under good resource conditions, as these provide better chances of surviving dispersal and gaining fitness benefits such as avoiding kin competition and inbreeding. Individual traits should mediate the effect of resources, yielding a complex condition-dependent dispersal response. We investigated how experimental food reductions in a food-rich environment around poultry-growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…During the winter, the amount of available food is relatively scarce [17, 46] without anthropogenic food subsidies (S1 Film). With these, as in our study area, jackals were the heaviest in the December-April period, which is also the mating season of the jackal [40], which is associated with more intense daily and territorial activity [11, 21, 31] and therefore greater energy requirements. Although the amount of the big game viscera drastically declined in spring and summer (period of pupping or calving and early parental care), carcasses were still available in large numbers during this period (it was impossible to remove them all).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During the winter, the amount of available food is relatively scarce [17, 46] without anthropogenic food subsidies (S1 Film). With these, as in our study area, jackals were the heaviest in the December-April period, which is also the mating season of the jackal [40], which is associated with more intense daily and territorial activity [11, 21, 31] and therefore greater energy requirements. Although the amount of the big game viscera drastically declined in spring and summer (period of pupping or calving and early parental care), carcasses were still available in large numbers during this period (it was impossible to remove them all).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the second survey, reproduction among one-year old females was also observed. Presumably, food reduction in less productive areas [5, 21] compared to areas of high ungulate density can result in greater impacts of decreasing population density and survival, and increasing home range size of medium-sized canids. To better understand the ecology of the jackal, during a long-term period, for example population size, reproduction and habitat use, parallel with feeding habits should be analysed in relation to food abundance (or: amount of food available).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Matthysen () suggests that increased population density can modify habitat quality, influencing dispersal propensity, for example, western bluebirds ( Sialia mexicana ) produce more aggressive young with high dispersal propensity when nest cavities are limited (Potticary & Duckworth, ). Kapota et al () in an experiment, restricting food sources, found an increased dispersal propensity in golden jackals ( Canis aureus ); however, under the same conditions red foxes ( Vulpes vulpes ) did not show an increased dispersal propensity. Erigone arctica and E. dentiplapis when starved also showed a decreased propensity to disperse (Bonte, Lukáč, & Lens, ), while increased density dependence did not impact female red deer ( Cervus elaphus ), but decreased male dispersal propensity and increased dispersal distance (Loe, Mysterud, Veiberg, & Langvatn, ).…”
Section: Discussionmentioning
confidence: 91%